2010
DOI: 10.1166/jnn.2010.2904
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Luminescence of Azobenzene Capped CdS Quantum Dots

Abstract: Cadmium sulfide (CdS) quantum dots (QDs) are prepared at room temperature by "form-fill-seal" method, while the azobenzene is used as surfactant to control the particle size and to prevent agglomeration. The typical size of CdS nanoparticles is estimated as 2 nm by X-ray diffraction. The absorption spectra of CdS QDs are measured at room temperature and a new absorption peak associated with the surface excited state is found. The luminescence property of the CdS QDs is studied at room temperature and low tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…These images revealed that GCDs can efficiently attach to the bacterial cell surface. The mechanism may be ascribed to the tiny spherical CDs obtained from gram shells, with surface carboxylic acids binding to the bacterial cells more rapidly than other microbial organisms [71][72][73][74]. A gram shell is a highly abundant source of carbohydrates (approx.…”
Section: Gcds As Fluorescent Imaging Probe For Gram-negative Bacteria...mentioning
confidence: 99%
“…These images revealed that GCDs can efficiently attach to the bacterial cell surface. The mechanism may be ascribed to the tiny spherical CDs obtained from gram shells, with surface carboxylic acids binding to the bacterial cells more rapidly than other microbial organisms [71][72][73][74]. A gram shell is a highly abundant source of carbohydrates (approx.…”
Section: Gcds As Fluorescent Imaging Probe For Gram-negative Bacteria...mentioning
confidence: 99%
“…There are a large number of reports on the application of CdS QDs in the field of photocatalysis [13,14], solar cells [15], X-ray detectors [16], laser screen materials [5], projection color TVs [17], nuclear radiation detectors [17], LEDs [18], luminescence probes and bio-organic detectors [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…AB has already been synthesized with QDs, either as capping ligands on CdS QDs [18] or as a way to reversibly assemble and disassemble a suprastructure of gold nanoparticles [19]. However, no experimental or theoretical research has investigated the questions of mobility and conductance in QDs linked by reversible molecules such as AB.…”
Section: Introductionmentioning
confidence: 99%